2008
DOI: 10.1063/1.2837195
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic-assisted magnetic-field-induced strain and stress output of Ni–Mn–Ga single crystal

Abstract: Articles you may be interested indc-and ac-magnetic field-induced strain effects in ferromagnetic shape memory composites of Ni-Mn-Ga single crystal and polyurethane polymer J. Appl. Phys. 107, 09A942 (2010); 10.1063/1.3357408 Large magnetic-field-induced strains in Ni-Mn-Ga nonmodulated martensite Appl. Phys. Lett. 95, 104103 (2009); 10.1063/1.3227661Acoustic-assist effect on magnetic threshold field and twinning-yield stress of Ni-Mn-Ga single crystals

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 8 publications
1
15
0
Order By: Relevance
“…The load amplitude of the actuator without acoustic assistance at low frequency (10 Hz) is calculated to be 7.95 N or 0.99 MPa. The resulting load corresponds well with the previous report [17] that, under quasi-static actuation, the stress output from FSMA actuators is typically limited in the range between 0.8 -1.5 MPa, because the magnetic energy that is coupled into a material is limited by the anisotropy energy, K u .…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…The load amplitude of the actuator without acoustic assistance at low frequency (10 Hz) is calculated to be 7.95 N or 0.99 MPa. The resulting load corresponds well with the previous report [17] that, under quasi-static actuation, the stress output from FSMA actuators is typically limited in the range between 0.8 -1.5 MPa, because the magnetic energy that is coupled into a material is limited by the anisotropy energy, K u .…”
Section: Resultssupporting
confidence: 66%
“…It is also reported that the cyclic reversible strain of the Ni-Mn-Ga single crystal increases from 0.03 to 0.045 with an acoustic-assist technique. The larger strain appears over a broader range of stress output [17]. As a result, the acoustic-assist technique is shown to increase the efficiency of an FSMA device in delivering mechanical energy σ bias ε out .…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The high-temperature limit is usually imposed by the transition temperature of the reverse martensitic transition. The presence of an acoustic drive has been proposed in order to improve twin-boundary mobility thus making the magnetic shape memory effect more efficient (Techapiesancharoenkij et al, 2008a). It was shown that a small amplitude acoustic signal generated by means of a piezoelectric actuator is suitable to reduce the threshold field and to achieve greater strains under a smaller magnetic field.…”
Section: Twin-boundary Motionmentioning
confidence: 99%
“…It is evident from the literature that the FSMAs have ferromagnetic nature and undergo martensite transformation (Ullakko et al 1996;Mullner and Ullakko 1998;Mullner et al 2002;Chernenko et al 2007;Techapiesancharoenkij et al 2008). The phase transformation and energy dissipation through twin mechanism in Ni-Mn-Ga makes it a suitable candidate for dampers.…”
Section: Introductionmentioning
confidence: 98%